Hybrid treatment of an aortic arch aneurysm in a patient with a patent right and left internal mammary graft. (February 2013) - Gemayel, Gino; Murith, Nicolas; Mugnai, Damiano; Khabiri, Ebrahim; Kalangos, Afksendiyos
The aim of this report is to describe a known hybrid surgical and endovascular technique for aortic arch aneurysm repair in a special setting of a patient with previous coronary mammary bypass. We present a case of aortic arch aneurysm in a 66-year-old man with previous coronary bypass. He underwent a hybrid endovascular and surgical repair. All supraaortic vessels were debranched, keeping a continuous antegrade blood flow through the left and right internal mammary arteries to avoid myocardial ischemia. Endovascular treatment of aortic arch aneurysms is associated with less mortality and morbidity as compared with open surgery. The hybrid procedure with surgical debranching of the supraaortic vessels is the most commonly used method. In cases of previous coronary bypass with mammary arteries, care must be taken to maintain constant flow through the grafts during debranching.